Hybrid health research: Assembling an integrated arts/science methodological framework. (1st August 2017) - Edwards, Geoffrey; Arfaoui, Afnen; McLaren, Coralee; McKeever, Patricia
Within the effort to create a form of enquiry that is both, and neither, art and science, we explore methodologies at the intersection of these activities. The methodologies under study are grounded in embodied contemporary philosophical writings – the work of Gibson, Deleuze and Guattari and Whitehead have drawn our particular interest. Using examples drawn from projects undertaken over recent years, we illustrate how these philosophies can be used to develop a formal methodological framework. We then go on to investigate to what extent the elements that form this framework are also found in a corpus of texts obtained from interviews with researchers and students working in arts-based health research. The results, which largely confirm the lessons drawn, suggest that the proposed framework may have broader generality.